Hypothermic machine perfusion of the liver and the critical balance between perfusion pressures and endothelial injury. - 't Hart, N; van der Plaats, A; Leuvenink, H; van Goor, H; Wiersema-Buist, J; Verkerke, G; Rakhorst, G; Ploeg, R (2005)
Hypothermic machine perfusion (HMP) provides better protection against cold ischemic injury than cold storage in marginal donor kidneys. Also, in liver transplantation a switch from static cold storage to HMP could be beneficial as it would allow longer preservation times and the use of marginal donors. A critical question concerning application of HMP in liver preservation is the crucial balance between perfusion pressure and occurrence of endothelial injury. Rat livers were cold-perfused for 24 hours to study perfusion pressures for both hepatic artery and portal vein. Cold storage served as control and was compared to HMP-preserved livers using a mean arterial perfusion pressure of 25 mm Hg and a portal perfusion pressure of 4 mm Hg (25% of normothermic liver circulation) and to HMP at 50 mm Hg and 8 mm Hg perfusion, respectively (50% of normothermic liver circulation). UW solution was enriched with 14.9 micromol/L propidium iodide (PI) to stain for dead cells and with an additional 13.5 micromol/L acridine orange to stain for viable hepatocytes. A low PI-positive cell count was found using HMP at 25% of normal circulation compared to cold storage. The PI count was high for the HMP group perfused at just 50% of normal circulation compared to HMP at 25% and compared to cold storage. In summary, for liver HMP, perfusion at 25% showed complete perfusion with minimal cellular injury. HMP using perfusion pressures of 25 mm Hg for the hepatic artery and 4 mm Hg for the portal vein is feasible without induction of endothelial injury.